Integral Transforms and Operational Calculus - Srivastava, Hari Mohan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Researches and investigations involving the theory and applications of integral transforms and operational calculus are remarkably wide-spread in many diverse areas of the mathematical, physical, chemical, engineering and statistical sciences.